The Influence Of Internal Audit On Financial Performance - Erpi Rahman; Nining Kurniasih; Reni Nurkhofifah (Journal of Business, Accounting and Finance, 2022)
This study aims to determine how the implementation of internal audit and the company's financial performance, and to find out how the influence of internal audit on the financial performance of PT. Engineering Nut. The factors tested in this study were internal audit as the independent variable, while financial performance as the dependent variable. The research method used in this research is descriptive and verification method. The population in this research is internal audit, manager, finance department and annual report at PT. Engineering Nut. The data analysis used in this research is simple linear regression analysis at a significance level of 5%. The program used in analyzing the data uses SPSS vers 28. The results show that the implementation of internal audit at PT. Mura Teknik is included in the good category. While the financial performance of PT. Mura Teknik is in the good category. In addition, the results of the study also show that internal audit has an effect on financial performance. The magnitude of the influence of internal audit in contributing to financial performance is 48.1%.